Evaluation of Bookkeeping, Inventory, and Reporting of Regional Owned Goods is Based on Permendagri No. 47 of 2021 at the City BAPENDA Bitung - Lombogia, Enjelina Maria Heske; Pangerapan, Sonny; Kapojos, Peter M. (Formosa Journal of Applied Sciences, 2024)
This research aims to evaluate the bookkeeping, inventory and reporting of regional property based on Minister of Home Affairs Regulation Number 47 of 2021 concerning Procedures for Implementing Bookkeeping, Inventory and Reporting of Regional Property at BAPENDA Bitung City. The implementation of these regulations at the Bitung City Regional Revenue Agency (BAPENDA) is still facing challenges and problems. This type of research is qualitative research with approach descriptive. The research results show that the Bookkeeping, Inventory and Reporting of Regional Property has been carried out appropriately by the Bitung City Regional Revenue Agency by following the Minister of Home Affairs Regulation (Permendagri) Number 47 of 2021 concerning Procedures for Bookkeeping, Inventory and Reporting of Regional Property.